Product Formulation of Ready to Use Fish Food (RUFF) from Snakehead Fish Flour (Channa striata) - Puspo Edi Giriwono; Safira P.A Haryanto; Saraswati Saraswati (The University of Lampung, 2025)
RUFF (ready-to-use fish food) is a nutrient and calorie-dense food with high protein and energy consumed by children under five years of age who suffer from severe acute malnutrition. RUFF in this study was designed to be the alternative product for RUTF (ready-to-use therapeutic food) using snakehead fish flour as skim milk substitute. This study aims to determine the suitability of snakehead fish flour as an animal protein alternative, obtain the RUFF formula that meets FAO and WHO standards, and determine the consumer acceptance. The research investigated different amount of snakehead fish flour in the RUFF formulation. There were 3 formulas with different snakehead fish flour, i.e. 20% (F1), 22% (F2), and 24% (F3). The results of the analysis showed that the highest protein content was found in formula F3 (14.35 ±0.72)% with moisture content of 2.32 ± 0.06%, ash content of 2.56 ± 0.04%, fat content of 29.39 ± 0.24%, and carbohydrate content of 51.37 ± 0.94%. All three RUFF formulations meet the nutritional standards set by the FAO and WHO. The hedonic rating test results and ranking showed that the most preferred formula by the panelist was formula F1 containing 20% snakehead fish flour with an average rate of 7.46 (like). Formula F1 is the formula of RUFF with the highest rate of consumer acceptance.